PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Rosyida Alfi Qonitin; Siska Priyandani Yudowati (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2018)
This study aims to examine the effects of corporate governance mechanisms proxyed with institutional ownership, independent commissioners and audit committees, and the effect of audit quality on the integrity of financial statements simultaneously and partially. The population in this research is Mining Company registered in Indonesia Stock Exchange (BEI). Sample selection technique used is purposive sampling and obtained 9 companies with research period year 2012-2016. Data analysis method used in this research is panel data regression analysis using software Eviews version 9. The results show that institutional ownership, independent commissioners, audit committee, and audit quality simultaneously affect the integrity of financial statements. While partially, institutional ownership, independent commissioners have no effect on the integrity of financial statements. Audit committee and audit quality have an effect on to integrity of financial statement.